Factors Influencing The Intention To Implement Accounting Software In The Preparation Of Financial Statements At Umkm In The Sub-District Of Sukarami Palembang - Addellia, Addellia; Vegirawati, Titin; Pandriadi, Pandriadi (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the factors that influence the intention of MSME actors in implementing accounting software for preparing financial reports. The factors analyzed are perceived usefulness, perceived ease of use, and trust. Accounting software includes Zahir, MS Excel, MokaPos, and others. helps MSMEs in recording and processing financial transactions and preparing financial reports practically, financial reports are important because they can be used as a basis for assessing business feasibility, this is one of the requirements for obtaining support for capital, and can develop business. This research uses a quantitative approach to analyze primary data obtained through distributing questionnaires to 323 MSME actors in Sukarami District, Palembang. Data analysis was conducted using Partial Least Square. The results showed that perceived ease of use and trust had a significant effect on the intention to implement accounting software, while perceived usefulness did not show a significant effect on the intention to implement accounting software in preparing financial statements.